Another look at foreign aid - Gustav Ranis (Yale University, Economic Growth Center, 2012)
The discussion of the effectiveness of foreign aid has reached a high pitch. This paper assesses the sorry past and present key arguments for a potentially more effective and sustainable method of aid delivery. A key ingredient is to shake off the vestiges of structural adjustment and move towards true recipient country ownership complete with 'self-conditionality' with aid recipients formulating their own reform packages. This means donors become much more passive, act like a bank and respond to proposals which concentrate on a few critical areas over a three to five-year period. Policy-based program lending should respond to packages put together by the main domestic stakeholders with the help, if necessary, of independent third parties. There should be no compulsion to lend; indeed, an aid hiatus is an indication that the new system is effective. What is required is for donors to stop using aid as a short-term foreign policy tool and for recipients to accept the notion that aid provides the opportunity to reduce the inevitable adjustment pains caused by real reforms.
Keywords: O11; O20; O38; P45; 330; Foreign aid; self-conditionality; program lending; new donors; Foreign aid; self-conditionality; program lending; new donors